Peony in love ebook A novel. - See, Lisa (2007)
NEW YORK TIMES BESTSELLER •  “A complex period tapestry inscribed with the age-old tragedy of love and death.”— The New York Times Book Review “I finally understand what the poets have written. In spring, moved to passion; in autumn only regret.” In seventeenth-century China, in an elaborate villa on the shores of Hangzhou’s West Lake, Peony lives a sheltered life. One night, during a theatrical performance in her family’s garden, Peony catches sight of an elegant, handsome man and is immediately overcome with emotion. So begins Peony’s unforgettable journey of love and destiny, desire and sorrow, the living world and the afterworld. Eventually expelled from all she’s known, Peony is thrust into a realm where hungry ghosts wander the earth, written words have the power to hurt and kill, and dreams are as vivid as waking life. Lisa See’s novel, based on actual historical events, evokes vividly another time and place—where three generations of women become enmeshed in a dramatic story, uncover past secrets and tragedies, and learn that love can transcend death. Peony in Love will make you ache in heart and mind for young Peony and all the women of the world who want to be heard. BONUS: This edition contains an excerpt from Lisa See's  Shanghai Girls . Praise for Peony in Love “Electrifying . . . a fascinating and often surprising story of women helping women, women hurting women and women misunderstanding each other.” — The Miami Herald “See mines an intriguing vein of Chinese history . . . weaving fact and fiction into a dense romantic tapestry of time and place as she meditates on the meaning of love, the necessity of self-expression and the influence of art.” — Los Angeles Times “A transporting read, to lost worlds earthly and otherwise.” — Chicago Tribune “A quietly beautiful tale that sneaks into the reader’s heart . . . Not since Susie Salmon of Alice Sebold’s The Lovely Bones  has a ghostly narrator been as believable and empathetic.” — San Antonio Express-News “There’s much here to be savored and a great deal to be learned.” — The Washington Post Book World